Atherothrombotic risk stratification after acute myocardial infarction: The Thrombolysis in Myocardial Infarction Risk Score for Secondary Prevention in the light of the French Registry of Acute ST Elevation or non‐ST Elevation Myocardial Infarction registries. Issue 2 (27th December 2018) - Puymirat, Etienne; Bonaca, Marc; Fumery, Maxime; Tea, Victoria; Aissaoui, Nadia; Lemesles, Gilles; Bonello, Laurent; Ducrocq, Grégory; Cayla, Guillaume; Ferrières, Jean; Schiele, François; Simon, Tabassome; et al.
Abstract : Background: Guidelines recommend using risk stratification tools in acute myocardial infarction (AMI) to assist decision‐making. The Thrombolysis in Myocardial Infarction Risk Score for Secondary Prevention (TRS‐2P) has been recently developed to characterize long‐term risk in patients with MI. Hypothesis: We aimed to assess the TRS‐2P in the French Registry of Acute ST Elevation or non‐ST elevation MI registries. Methods: We used data from three 1‐month French registries, conducted 5 years apart, from 2005 to 2015, including 13 130 patients with AMI (52% ST‐elevation myocardial infarction [STEMI]). Atherothrombotic risk stratification was performed using the TRS‐2P score. Patients were divided in to three categories: G1 (low‐risk, TRS‐2P = 0/1); G2 (intermediate‐risk, TRS‐2P = 2); and G3 (high‐risk, TRS‐2P ≥ 3). Baseline characteristics and outcomes were analyzed according to TRS‐2P categories. Results: A total of 12 715 patients (in whom TRS‐2P was available) were included. Prevalence of G1, G2, and G3 was 43%, 24%, and 33% respectively. Clinical characteristics and management significantly differed according to TRS‐2P categories. TRS‐2P successfully defined residual risk of death at 1 year (C‐statistic 0.78): 1‐year survival was 98% in G1, 94% in G2, and 78.5% in G3 ( P < 0.001). Using Cox multivariate analysis, G3 was independently associated with higher risk of death at 1 year (hazard ratio [HR] 4.61; 95% confidence interval [CI]: 3.61‐5.89), as G2 (HR 2.08; 95% CI: 1.62‐2.65) compared with G1. The score appeared robust and correlated well with mortality in STEMI and NSTEMI populations, as well as in each cohort separately. Conclusions: The TRS‐2P appears to be a robust risk score, identifying patients at high risk after AMI irrespective of the type of MI and historical period.